Review; Efektivitas Tanaman Herbal Sebagai Anti Nyamuk Yang Mampu Mematikan Nyamuk Aedes Aegypti - Muhammad Ikhsanul Kahfi; Siti Fauziah Ahmad; Assyifa Rachma Citra; Firdha Senja Maelaningsih (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The fastest-growing disease transmitted by the Aedes aegypti mosquito in the world is Dengue Hemorrhagic Fever. Controlling mosquito populations alone is not enough. However, mosquito larvae also need to be managed well. Certain herbal plants can be used to control mosquito larvae. With the development of technology, there are various types of mosquito repellent models. Among them are electric forms and anti-mosquito burns, which contain chemicals and which, if continued to be used in the long term, will cause more effects of respiratory diseases. One way to prevent this is by using insecticides derived from herbal plant extracts. The purpose of this review article is to determine the effectiveness of herbal plants for killing Aedes aegypti mosquitoes using several herbal plants, such as basil leaves, gadung tubers, lemongrass, and alang-alang using experimental methods with several concentrations, which were taken based on the journals used in 4 main literature, with a time span of the last ten years, namely 2013-2023. The results of this review are that all the herbal plants used were proven to be effective in killing Aedes aegypti mosquitoes at various concentrations.